Apreçamento de opções de recompra embutidas: uma aplicação ao mercado de debêntures brasileiro - Pereira, Leonardo Tavares (2010)
In this work we develop a strategy to price embedded options. This kind of options exists in a large number of debentures in the Brazilian market. As this market presents a reduced number of assets, pricing the embedded options is necessary so as to increase the number of assets available to analysis. As an intermediary step, we need to know when is interesting to the issuer to call the debenture before the expiration date. With this intuit, we propose a methodology to estimate the term structure of the debentures market based on the model of Nelson-Siegel. As an exercise, we apply the proposed strategy to estimate the embedded option on the debenture TSPP22. We observed that the value of this option presented an ascendant behavior during the analyzed period. As matter of fact, this debenture was called by the issuer on February of 2011.